Reconciling hierarchy and democracy: the value of management learning - Clarke, Martin; Butcher, David (Sage Publications, 2006)
Pluralistic organizations are often argued to have become an indisputable reality for senior managers. In consequence, the role of hierarchy has come under close scrutiny. How can organizations balance the need for congruence, provided through hierarchy, with the need for greater organizational democracy? As yet, the potential for management education and learning to impact on this debate, at either an organizational or a societal level, has been largely unfulfilled. This article argues that the aspirational values of liberal adult educationalists have a significant contribution to make to the management of contemporary organizations. It positions these values alongside the business requisites that shape organizations and examine the motivations of senior managers to apply these ideas in practice. The concept of voluntarism, derived from the field of political philosophy, is proposed as an alternative organizational binding mechanism that alters the rationale for the role of hierarchy. The implications for senior executives and management educationalists are considered.
Keywords: adult education; communitarianism; hierarchy; organizational democracy; voluntarism